Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1111/j.1540-8159.1991.tb02760.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonphysiological Left Heart AV Intervals as a Result of DDD and AAI “Physiological” Pacing

Abstract: DDD and AAI pacemakers are considered physiological, since they preserve atrioventricular (AV) synchrony. Artificial pacing, however, is performed largely from right heart chambers, causing aberrant depolarization pathways. Pacing at the right atrial appendage (RAP) is known to delay left atrial contraction due to interatrial conduction time (IACT), and right ventricular (RV) apical pacing (RVP) delays left ventricular (LV) contraction due to interventricular conduction time (IVCT). These delays may render the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Symptoms cleared and exercise tolerance improved after a DDD pacemaker with a relatively short AV interval (100 ms) was implanted. This observation and several other publications 3,4 , 20–22 led to the conclusion that the left heart AV is the key determinant of cardiac performance, even at the expense of not entirely “normal” right heart AV or PR intervals.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Symptoms cleared and exercise tolerance improved after a DDD pacemaker with a relatively short AV interval (100 ms) was implanted. This observation and several other publications 3,4 , 20–22 led to the conclusion that the left heart AV is the key determinant of cardiac performance, even at the expense of not entirely “normal” right heart AV or PR intervals.…”
Section: Discussionmentioning
confidence: 53%
“…Numerous publications attribute the nonphysiological nature of right heart DDD pacing to several pacing and sensing induced delays, thus increasing the acceptance of the left heart AV interval as an independent entity 3,4 , 12 , 25,26 . In heart failure patients, in whom the proper AV sequence may be critical, it was shown that there was clinical improvement when patients with LBBB and first‐degree AV block were paced with short AV interval 27–30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right atrial pacing may reveal or enhance atrial conduction disorders depending on the site and rate of atrial pacing 35 , 116 (Fig. 6).…”
Section: Hemodynamic Consequences Of Intra‐ and Interatrial Conductiomentioning
confidence: 99%
“…6). Several studies 116‐119 have shown the wide interindividual variability of intra‐ and interatrial conduction times in patients with pacemakers. In the series by Wish et al 118 the duration of interatrial conduction time in paced atrial cycles varied from 70 to 380 ms (mean 144 ± 82 ms).…”
Section: Hemodynamic Consequences Of Intra‐ and Interatrial Conductiomentioning
confidence: 99%